The Relationship of Socio-Economic with Nutritional Status in Toddlers in Meureubo Sub-District West Aceh Regency - Khairunnas Khairunnas; Arfah Husna; Marniati Marniati (Journal of Nutrition Science, 2020)
Children's health and growth are issues that need continuous attention by various parties, such as the government and family. As a result of malnutrition status in infancy can cause growth retardation, causing toddlers to be lazy to do activities related to energy production, disruption of the toddler's immune system so they are susceptible to infectious diseases, inhibited optimal brain growth, and changes in behavior exhibited by toddlers such as not calm, easy crying and its ongoing impact is apathetic behavior. Based on the preliminary survey in the Meurebo Sub-District, West Aceh Regency, there were 4 toddlers suffering from malnutrition and 11 people with underweight nutritional status. The aims of study was to look at the socio-economic relationship with nutritional status of toddlers. This study uses quantitative research with a cross-sectional approach using a chi-square test with a standard error of 0.05. The population of this study were 46 peoples with those taken based on sample distribution. The results obtained by the value of sig = 0.007 which means smaller than the value of α = 0.05, so it can be concluded a significant relationship between socio-economic and nutritional status of toddler